2016
DOI: 10.3389/fpsyg.2016.01690
|View full text |Cite
|
Sign up to set email alerts
|

Describe Your Feelings: Body Illusion Related to Alexithymia in Adolescence

Abstract: Objective: Having access to bodily signals is known to be crucial for differentiating the self from others and coping with negative feelings. The interplay between bodily and emotional processes develops in adolescence, where vulnerability is high, as negative affect states often occur, that could hamper the integration of bodily input into the self. Aim of the present study in healthy adolescents was to examine, whether a disturbed emotional awareness, described by the alexithymic construct, could trigger a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…A body of research has demonstrated that the way emotions are processed and experienced also has an impact on the sense of body ownership. To name one example, higher scores in an alexithymia questionnaire were associated with a stronger illusion in a study with adolescents 10 . Hence, differences in emotion experience could influence the relationship of emotions and sense of body ownership.…”
Section: Introductionmentioning
confidence: 99%
“…A body of research has demonstrated that the way emotions are processed and experienced also has an impact on the sense of body ownership. To name one example, higher scores in an alexithymia questionnaire were associated with a stronger illusion in a study with adolescents 10 . Hence, differences in emotion experience could influence the relationship of emotions and sense of body ownership.…”
Section: Introductionmentioning
confidence: 99%
“…Research generally supports this idea, although the direction of effects is mixed, with some studies linking alexithymia to exaggerated neural, physiological, or behavioral responses to exteroceptive or body-based cues (e.g., Sivik, 1993 ; Nyklicek and Vingerhoets, 2000 ; Schafer et al, 2007 ; Bogdanov et al, 2013 ) and others linking it to reduced responsiveness (e.g., Pollatos et al, 2008 ; Goerlich-Dobre et al, 2014b ; Gaigg et al, 2018 ). Alexithymia is also associated with atypicalities in multisensory integration, although the direction of the effects has varied (see Miles et al, 2011 ; Thakkar et al, 2011 ; Cascio et al, 2012 ; Germine et al, 2013 ; Grynberg and Pollatos, 2015 ; Georgiou et al, 2016 ). The mixed results from studies in this area could reflect the fact that researchers have not typically considered in their study designs the possibility that there may be subtypes of individuals with alexithymia who generate, experience, and regulate their emotions in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…These latter findings demonstrate a mismatch between objective and subjective aspects of body awareness, possibly impacting emotional processing and 'sense of self'. Indeed, alexithymic subjects show reduced emotional awareness (Lane et al, 2015) and higher malleability of body representation in illusions of body-ownership (Georgiou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%